Dialysis-associated pathogens at King Fahad Hospital of the University, Eastern Province, Saudi Arabia - Abu Quren, Ahmed M.; Alfaraj, Abdullah A.; Al Wuhayb, Hassan S.; Alabdullah, Hussain A.; Alowayshir, Yousef A.; Alhaiz, Abdullah A.; Hunasemarada, Basavaraja C.; El-Badry, Ayman A. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Microbial infection among dialysis patients is a major health problem with several outcomes including morbidity, mortality, as well as hospitalization. Detection of the prevailing pathogens and their predictors in dialysis patients is crucial to their management and prevention. Methods: A retrospective observational study was conducted in King Fahd Hospital of the University to illustrate the burden of dialysis-associated pathogens, and to assess the association between patients’ characteristics and the occurrence of infection and their role as predictors. Results: The study included all patients who underwent dialysis and had associated infections confirmed by blood culture between 1990 to 2022. A total of 485 dialysis patients were included in the study. Half of the dialysis patients (51%) had pathogenic infections. The most common pathogen among hemodialysis was Staphylococcus aureus followed by Pseudomonas aeruginosa. In peritoneal dialysis, the most common pathogen was Staphylococcus aureus followed by Staphylococcus epidermis. Old age (61-80 years), male sex, and hemodialysis were associated with an increased risk of infection (P value <0.05). Conclusion: Bacteria, namely Staphylococcus aureus, Pseudomonas aeruginosa and Staphylococcus epidermis, were the most common pathogens in dialysis patients. Among all studied patients’ characteristics only old age (60-80 years) and being male was associated with the occurrence of infection in all dialysis patients.